MRI Evidence: Acute Mountain Sickness Is Not Associated with Cerebral Edema Formation during Simulated High Altitude - Mairer, Klemens; Göbel, Markus; Defrancesco, Michaela; Wille, Maria; Messner, Hubert; Loizides, Alexander; Schocke, Michael; Burtscher, Martin (PLOS ONE, 2012)
Acute mountain sickness (AMS) is a common condition among non-acclimatized individuals ascending to high altitude. However, the underlying mechanisms causing the symptoms of AMS are still unknown. It has been suggested that AMS is a mild form of high-altitude cerebral edema both sharing a common pathophysiological mechanism. We hypothesized that brain swelling and consequently AMS development is more pronounced when subjects exercise in hypoxia compared to resting conditions. Twenty males were studied before and after an eight hour passive (PHE) and active (plus exercise) hypoxic exposure (AHE) (FiO2 = 11.0%, PiO2∼80 mmHg). Cerebral edema formation was investigated with a 1.5 Tesla magnetic resonance scanner and analyzed by voxel based morphometry (VBM), AMS was assessed using the Lake Louise Score. During PHE and AHE AMS was diagnosed in 50% and 70% of participants, respectively (p>0.05). While PHE slightly increased gray and white matter volume and the apparent diffusion coefficient, these changes were clearly more pronounced during AHE but were unrelated to AMS. In conclusion, our findings indicate that rest and especially exercise in normobaric hypoxia are associated with accumulation of water in the extracellular space, however independent of AMS development. Thus, it is suggested that AMS and HACE do not share a common pathophysiological mechanism.